Effects of dynamic lighting on circadian phase, self‐reported sleep and performance during a 45‐day space analog mission with chronic variable sleep deficiency. Issue 4 (5th September 2022) - Rahman, Shadab A.; Kent, Brianne A.; Grant, Leilah K.; Clark, Toni; Hanifin, John P.; Barger, Laura K.; Czeisler, Charles A.; Brainard, George C.; St Hilaire, Melissa A; Lockley, Steven W.
Abstract: Spaceflight exposes crewmembers to circadian misalignment and sleep loss, which impair cognition and increase the risk of errors and accidents. We compared the effects of an experimental dynamic lighting schedule (DLS) with a standard static lighting schedule (SLS) on circadian phase, self‐reported sleep and cognition during a 45‐day simulated space mission. Sixteen participants (mean age [±SD] 37.4 ± 6.7 years; 5 F; n = 8/lighting condition) were studied in four‐person teams at the NASA Human Exploration Research Analog. Participants were scheduled to sleep 8 h/night on two weekend nights, 5 h/night on five weekday nights, repeated for six 7‐day cycles, with scheduled waketime fixed at 7:00 a.m. Compared to the SLS where illuminance and spectrum remained constant during wake ( 4000K), DLS increased the illuminance and short‐wavelength (blue) content of white light ( 6000K) approximately threefold in the main workspace (Level 1), until 3 h before bedtime when illuminance was reduced by 96% and the blue content also reduced throughout ( 4000K × 2 h, 3000K × 1 h) until bedtime. The average (±SE) urinary 6‐sulphatoxymelatonin (aMT6s) acrophase time was significantly later in the SLS (6.22 ± 0.34 h) compared to the DLS (4.76 ± 0.53 h) and more variable in SLS compared to DLS (37.2 ± 3.6 min vs. 28.2 ± 2.4 min, respectively, p = .04). Compared to DLS, self‐reported sleep was more frequently misaligned relative to circadian phase in SLS RR: 6.75, 95% CI 1.55–29.36, p = .01), but neither self‐reported sleep duration nor latency to sleep was different between lighting conditions. Accuracy in the abstract matching and matrix reasoning tests were significantly better in DLS compared to SLS (false discovery rate‐adjusted p ≤ .04). Overall, DLS alleviated the drift in circadian phase typically observed in space analog studies and reduced the prevalence of self‐reported sleep episodes occurring at an adverse circadian phase. Our results support incorporating DLS in future missions, which may facilitate appropriate circadian alignment and reduce the risk of sleep disruption.